Reaction time and movement accuracy in running target shooting - Viitasalo, J. T.; Keränen, T.; Mononen, K. M.; Norvapalo, K. (1999)
In running target shooting the shooter holds a loaded rifle in a ready position so that the rifle`s butt is at his/her waistline. After the target appears, he/she is allowed to lift the gun, to aim (follow the target) and to trigger. Since the time for executing a shot is limited (5 or 2.5 s), a fast reaction and an accurate lift are thought to be decisive for a successful performance. The purpose of this study was to investigate the lifting time and accuracy characteristics among elite and novice shooters. 27 male volunteers with some previous experience, but no systematic training background in rifle shooting, represented novice shooters. They were tested before and after a 12-week intensive running target shooting training period. The elite group consisted of 10 Finnish male running target shooters who had competed at international level. The tests consisted of 20 running target shots (slow run, 5 s) in a laboratory constructed specially for studying biomechanics of shooting. An optoelectronic shooting training and analysis system Noptel ST 2000 Sport (Noptel Inc., Finland) was used to detect the scores, and a micro video camera (Panasonic WV-KS152) was connected to the optical sight of the gun to record the lift phase. Using the video and a special constructed analysing program (Reflex Sport, Finland) the lifting time (LT) was calculated from the target appearance to the end of the lift. The x and y coordinates of the aiming point as well as of the bull`s-eye were determined, and the distance between them (AED=aiming error distance) was calculated at the end of the lift phase for each shot. Mean values and standard deviations (SD) of the 20 shots were calculated for the score, LT and AED for each subject. The SDs were used to describe the scatter (consistency) of the temporal and spatial parameters. The mean score was 9.72 for the elite group, and 6.45 and 7.46 for the novice group before and after the training, respectively. The LT of the elite group was shorter (t=2.65, p<.05) and it`s scatter smaller (t=2.12, p<.05) than those of the novice group (before training). Also the AED of the elite group was shorter (t=5.02, p<.001) and it`s scatter smaller (t=6.72, p<.05) than those of the novice group. Among the novice group the 12-week training period led to a decrease in LT (t=2.46, p<.05) and AED (t=2.27, p<.05), as well as to their smaller scatters (t=4.16, p<.001; t=2.92, p<.01, respectively). The results suggest that training leads to a faster and more accurate execution of the lift, and a smaller scatter in the temporal and spatial variables. This provides more time for aiming and triggering, and therefore better preconditions for successful scoring.